A customer relationship management ecosystem that utilizes multiple sources and types of information conjointly - Hussain, Omar; Chang, Elizabeth; Ramakonar, V.; Dillon, T. (Curran & Associates, 2012)
In the current economic, budget tightening and competitive times, organizations need to be customer focused and provide customized service to customers to ensure their loyalty. To achieve this, Customer Relationship Management (CRM) systems help organizations to deal with and answer various customer queries. However with a change in the type of information being created (for example from structured to semistructured), CRM systems have to make effective use of such information which may be in multiple information sources for effective knowledge management and knowledge synthesis in order to provide customized services to the customers. In this paper, we propose a Customer Relationship Management ecosystem that conjointly utilizes multiple information sources and information types to achieve this. We explain the architecture of the proposed CRM ecosystems framework and demonstrate its application in the real estate domain.